PENGUJIANKELUARAN SENSOR ULTRASONIK HCSR04SEBAGAI ALAT UKUR JARAK TERHADAP GANGGUAN GELOMBANG SUARA DARI LUAR (NOISE) - Ganjar Kurniawan Sukandi (Jurnal Online Sekolah Tinggi Teknologi Mandala, 2023)
The HC-SR04 type ultrasonic sensor has been tested as a non-contact distance measuring device. The test is carried out under the influence/without the influence of environmental sound waves that act as noise. Tests were carried out to determine the output characteristics of the HC-Sr04 sensor without interference and when given noise interference. The system built is a distance measuring instrument consisting of an HCSR04 sensor, Arduino Uno as a microcontroller and an LCD. The noise is given in the form of sound waves that work in the frequency range of 20 – 20,000 Hz. The results of the HC-SR04 sensor test show that the presence of noise has no effect with a correlation coefficient of 0.054. Meanwhile, without noise, the sensor output produces a high linearity relationship, with a correlation coefficient of 0.99. However, the error generator output value is proportional to the distance measured with an average error of 1.64%.